SISTEM PEMBUKTIAN PADA TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM KAITANNYA DENGAN HUKUM ACARA PIDANA - Nara Palentina Naibaho; Mahmud Mulyadi; Muhammad Hamdan; Mirza Nasution (Universitas Sumatera Utara, 2017)
ABSTRACT Muara District Court Teweh No. 194/Pid.Sus/2013/PN.Mtw, the accused was sentenced under electronic evidence in the form of sms while Ranai District Court's Decision No.20/Pid.B/2013/PN.Rni containing electronic documents as supporting evidence to ensnare convict. It brings need to be assessed on setting criminal offense of information and electronic transactions contained in the legislation, Strength evidence electronic evidence in criminal offenses of information and electronic transactions in relation to criminal procedural law and the role of electronic evidence in uncovering the truth of the law in the District Court's Decision Muara Teweh 194/ Pid.Sus/2013/PN.Mtw and Ranai District Court's Decision No.20/Pid.B/2013/ PN.Rni. Keywords: Evidence, Verification and Criminal Procedure Law